Thomas Merton: A Life in Letters, the Essential Collection - Nugent, Don Christopher (Cistercian studies quarterly, 2010)
The article reviews the book "Thomas Merton: A Life in Letters, the Essential Collection," edited by William H. Shannon and Christine M. Bochen.